The Influences of Antenatal Care, Postnatal Care and Early Initiation of Breastfeeding on an Exclusive Breastfeeding Pattern in the Working Area of Manukan Kulon Public Health Center at Surabaya City (Medico Legal Update, 2021)
Exclusive breastfeeding is very important for babies to maintain their immune system, brain intelligence,emotion stability and to protect babies from various diseases that are causes of death. Breastfeeding willalso benefit the mother, which will reduce blood loss during menstruation, restore maternal weight as beforepregnancy, reduce the risk of breast cancer, and uterine cancer. The purpose of this study was to determine theinfluences of antenatal care, postnatal care and early initiation of breastfeeding on an exclusive breastfeedingpattern. The samples used in this study were mothers who had babies aged 7-12 months in June to August2018 as many as 48 respondents in the working area of Manukan Kulon Health Center in Surabaya. Thisstudy used the descriptive and bivariate analyses. The obtained results were antenatal care (p = 0.001),postnatal care (p = 0.002) and early initiation of breastfeeding (p = 0,000). During pregnancy the majority ofmothers make complete antenatal care visits with a frequency of 10 times, antenatal care is very importantfor mothers, especially the pattern of breastfeeding. In addition to the importance of antenatal care visits,mothers who have given birth and are entering the postnatal care phase are required to make postnatal carevisits. Socialization from health workers and the support of closest people are required in order to achievethe exclusive breastfeeding.